Flame retardants : tris(2-butoxyethyl) phosphate, tris(2-ethylhexyl) phosphate and tetrakis(hydroxymethyl) phosphonium salts - Esch, G. J., van (Environmental health criteria., 2000)
Resumé franc. a špan.